"Anxious and traumatised": Users' experiences of maternity care in the UK during the COVID-19 pandemic. (November 2021) - Sanders, Julia; Blaylock, Rebecca
Abstract: Objective: The COVID-19 pandemic saw universal, radical, and ultra-rapid changes to UK National Health Services (NHS) maternity care. At the onset of the pandemic, NHS maternity services were stripped of many of the features which support woman and family centred care. In anticipation of unknown numbers of pregnant women and maternity staff potentially sick with COVID-19, services were pared back to the minimum level considered to be required to keep women and their babies safe. The aim of this survey was to understand the impact of COVID-19 public health messaging and pandemic-related service changes on users of maternity care in the UK during the pandemic. Methods: We conducted an online survey to explore user's experiences of COVID-19 public health messaging and 'socially-distanced' maternity care across the UK. The study population consisted of women who had experienced pregnancy after the 11th March 2020 (when the WHO declared a pandemic), whether or not they were still pregnant. We collected data between June and September 2020. We used framework analysis for the free-text data and generated descriptive statistics. Findings: Women were generally happy to adopt a precautionary approach and stringently social distance in the context of a relatively unknown pathogen and in an environment of extreme anxiety and uncertainty, but were acutely aware of the negative impacts. The survey found that the widespread changes to services caused unintended negative consequences including essential clinical care being missed, confusion over advice, and distress and emotional trauma for women. COVID-19 restrictions have resulted in women feeling their antenatal and postnatal care to be inadequate and has also come at great emotional cost to users. Women reported feeling isolated and sad in the postnatal period, but also frustrated and upset by a lack of staff to help them care for their new baby. Key conclusions: With growing evidence of the impact of the virus on pregnant women and an increased understanding of the unintended consequences of unclear public health messaging and overly precautious services, a more nuanced, evidence-based approach to caring for women during a pandemic must be prioritised. Implications for practice: All maternity services should ensure they have clear lines of communication with women to keep them updated on changing care and visiting arrangements. Services should ensure that opportunities to provide safe face-to-face care and access for birth partners and visitors are maximised.